Da teoria da ação comunicativa à ética do discurso : Habermas e o caráter emancipador da razão dialógica - Mendonça, Daniel Mota (2024)
This study undertakes a philosophical journey that begins with Jürgen Habermas’ Theory of Communicative Action and culminates in Discourse Ethics, exploring the emancipatory character of dialogical reason. Initially, the investigation focuses on the Theory of Communicative Action, with an emphasis on Habermas’ critique of the predominance of instrumental rationality in contemporary societies. This predominance, according to the philosopher, leads to the reification of human interactions and the colonization of the Lifeworld by systemic logics, represented by the market and administration. Next, the work advances to Habermas’ Discourse Ethics, investigating how this normative theory presents itself as a response to the communicative void caused by modern dynamics. Thus, the central objective is to trace a path that, starting from the critique of instrumental rationality, reveals the emancipatory potential of dialogical reason defended by Habermas. In this context, the study seeks to answer the following question: How can Habermas' Discourse Ethics offer a viable solution to the crisis of communicative rationality in modernity, given the predominance of instrumental rationality and the reification of social relations? How can this theory be applied as a normative framework for overcoming the dynamics of contemporary domination and alienation, especially with regard to the colonization of the Lifeworld by the spheres of the market and administration? Methodologically, the study uses a critical analysis of the works of Habermas and thinkers who influenced his theoretical formation, such as Immanuel Kant, in addition to a comprehensive bibliographical review that integrates different theoretical perspectives. The aim is not only to expose the philosophical and normative bases of Discourse Ethics, but also to demonstrate its applicability for social criticism and the construction of a more just and equitable society. Thus, the dissertation aims to highlight the contemporary relevance of Habermasian theory, highlighting its capacity to contribute to the decolonization of the Lifeworld and to the construction of a public sphere guided by justice and equity.